Dog hepatocytes are key effector cells in the liver innate immune response to Leishmania infantum. Issue 6 (18th December 2018) - Rodrigues, A.; Alexandre-Pires, G.; Valério-Bolas, A.; Santos-Mateus, D.; Rafael-Fernandes, M.; Pereira, M. A.; Ligeiro, D.; Nunes, T.; Alves-Azevedo, R.; Lopes-Ventura, S.; Santos, M.; Tomás, A. M.; et al.
Abstract: Hepatocytes constitute the majority of hepatic cells, and play a key role in controlling systemic innate immunity, via pattern-recognition receptors (PRRs) and by synthesizing complement and acute phase proteins. Leishmania infantum, a protozoan parasite that causes human and canine leishmaniasis, infects liver by establishing inside the Kupffer cells. The current study proposes the elucidation of the immune response generated by dog hepatocytes when exposed to L. infantum . Additionally, the impact of adding leishmanicidal compound, meglumine antimoniate (MgA), to parasite-exposed hepatocytes was also addressed. L. infantum presents a high tropism to hepatocytes, establishing strong membrane interactions. The possibility of L. infantum internalization by hepatocytes was raised, but not confirmed. Hepatocytes were able to recognize parasite presence, inducing PRRs [nucleotide oligomerization domain (NOD)1, NOD2 and Toll-like receptor (TLR)2] gene expression and generating a mix pro- and anti-inflammatory cytokine response. Reduction of cytochrome P 450s enzyme activity was also observed concomitant with the inflammatory response. Addition of MgA increased NOD2, TLR4 and interleukin 10 gene expression, indicating an immunomodulatory role for MgA. Hepatocytes seem to have a major role in coordinating liver's innate immune response against L. infantum infection, activating inflammatory mechanisms, but always balancing the inflammatory response in order to avoid cell damage.